Corrosion effects of CNT-nanofluids on different metals - Ismail, Ahmad Faris; Anuar, Asnida; Walvekar , Rashmi Gangasa; Yusaf, Talal F. (WIT Press, 2014)
This study aims to determine the corrosion rates of three different metals (copper, stainless steel, and aluminium alloy) using CNT-nanofluids. Nanofluids have been extensively studied in enhancing heat transfer rates of conventional base fluids due to its efficiency and high thermal conductivity. Carbon nanotube (CNT) based nanofluids have demonstrated significantly higher thermal conductivity compared to nanofluids based on other nanoparticles. Though transport properties of CNT-nanofluids including its thermal conductivity, density and viscosity have been studied by large scientific community, there are only few studies carried out on its physical properties especially their reaction towards corrosion of different metals. Therefore, this study is carried out to compare the corrosion rates of three different metals using four different engine coolants with the variation of temperature from 27˚C to 90˚C. The coolants deployed in this work include ethylene glycol, water, and CNT-nanofluids with two different concentrations of 0.1 wt% and 0.02 wt% CNT. The CNT-nanfluids are stabilized using the Gum Arabic (GA) as the dispersant. The results reveal that for each metal, the corrosion rates in water are the highest followed by ethylene glycol and CNT-nanofluids with 0.02 wt% and 0.1 wt%. Among the three metals, the highest rate of corrosion occurs to aluminium, followed by stainless steel and copper, for all coolants used in this experimental study. Finally, the rate of corrosion increases with the increase of temperature for all cases.